PELAKSANAAN URUSAN BIDANG KELAUTAN DAN PERIKANAN DI KABUPATEN KENDAL - R. OktaDasananta Bawono Putro, Amiek Soemarmi, Indarja (Diponegoro Law Journal, 2012)
Dynamics of Marine and Fisheries Policy at Kendal in response to the enactment of decentralization of authority in various areas as a consequence of the passing of the era of reform and regional autonomy. Kendal as coastal areas also helped respond to all changes to the decentralization of authority over policy implementation in the marine and fisheries sector experience as the climate dynamics of democratization in all spheres. This study aims to investigate the implementation of marine affairs and fisheries in Kendal and determine barriers to Kendal County Government, especially related field of marine affairs and fisheries, and what steps are done The research methodology used in this study is normative. The data used are primary data is data obtained directly from the field through interviews and secondary data in the form of literary study. Analysis of the data used is descriptive qualitative conclusions deductively withdrawal The results were obtained: 1) The field of maritime affairs and fisheries in Kendal only a small fraction of all administrative matters submitted epada Autonomous Region or District 31 Kota.Pemerintah determine governmental affairs handed over to the District, 1 (one) of them matters The field of marine and fisheries governance. Of 1 (one) Field of marine and fisheries, 9 (nine) Sub Division handed over to the autonomous regional government district / municipality. 9 (nine) Sub-division is a small part of all the fields that must be taken care of authority by the State Government on behalf of the rights of the State Controlling. 2) Barriers and effort in implementing the authority of government affairs and fisheries marine field is still very small, Kendal regency administration has not been a lot of obstacles. But the necessary further steps to comply with the provisions in force at this time, in accordance with the development of the state